E-Learning Curriculum Thematic Rejodadi Elementary School Use Method UML-Based Hybrid - Elsya Amalia, Aqbrila; Fairuzabadi, Muhammad; Wardani, Setia; Nor Azhari Azman, Mohamed (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2023)
The Ministry of Education and Culture of the Republic of Indonesia regulates regulation to education through the determination of SNP ie National Education Standards. The curriculum used in education in Indonesia is Curriculum 2013. Thematic integrated is a Suite implementation in the learning process using Curriculum 2013. Integrated thematic learning is learning by integrating several lesson contents into a theme. Rejodadi Elementary School is one institution with moderate education development moment this is working To always increase the quality of Good activity and service. The moment This Rejodadi Elementary School currently faces the Covid-19 pandemic, where is the learning process teach done fully online or online at home? There is online application or e-learning of course become a challenge alone for SD Rejodadi which was affected plague. The PHP programming language and MYSQL database are used in building system this. Method data collection using method studies literature, observation, and interviews. Based on matters, the author wants to create and design something E-learning application about material and questions For Rejodadi Elementary School students. Study This will take the title “E-Learning Curriculum Rejodadi Elementary School Thematic Use Hybrid-Based UML Methods.